Constructing a Global Technology Assessment : Insights from Australia, China, Europe, Germany, India and Russia - Hahn, Julia [Hrsg.]Ladikas, Miltos [Hrsg.] (KIT Scientific Publishing, 2019)
Worldwide simultaneous effects of technologies, international challenges such as climate change as well as shifting relationships between science and society call for approaches that can address these issues on a global level. This book examines the potential of Technology Assessment (TA), as an until now mainly national and Western concept, to take on this global level and provide answers to these pressing questions.